1980
DOI: 10.3168/jds.s0022-0302(80)83003-7
|View full text |Cite
|
Sign up to set email alerts
|

Induced Lactation in Dairy Ewes by Various Brief Hormone Treatments

Abstract: Hormonal induction of lactation in 40 nonpregnant dairy ewes was attempted by daily injecting subcutaneously 25 mg estradiol-17 beta and 70 mg progesterone for 7 consecutive days. After an interval of 7 days the following treatments were applied: group I (10 ewes), nothing; group II, (10 ewes), 10 mg dexamethasone and 30 mg prednisolone; group III (10 ewes), 10 mg dexamethasone, 30 mg prednisolone, 400 IU insulin; and group IV (10 ewes), 10 mg dexamethasone, 30 mg prednisolone, 400 IU insulin, and 40 mg prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

1982
1982
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
1
3
0
1
Order By: Relevance
“…As in this study, lactation induction has been used to assess mammary gland specific transgene performance in cattle (Van Berkel et al 2002 ;Brophy et al 2003), goats (Ebert et al 1994;Baguisi et al 1999;Cammuso et al 2000) and even in pigs (Shamay et al 1992). The efficiency of what has become the standard oestrogen/progesterone/dexamethasone regime was 89 % (8 out of 9 heifers on the first attempt, 100% ultimately) in this study and is similar to the efficiencies of 70-100% reported by others for prepubertal heifers (Smith & Schanbacher, 1973;Fulkerson & McDowell, 1975 ;Field et al 1979), sheep (Alifakiotis et al 1980) and goats (Cammuso et al 2000). Furthermore, in the current study there was no evidence that the presence of the transgene influenced the responsiveness of the heifer calves to the induction protocol.…”
Section: Induction Success In Heiferssupporting
confidence: 88%
“…As in this study, lactation induction has been used to assess mammary gland specific transgene performance in cattle (Van Berkel et al 2002 ;Brophy et al 2003), goats (Ebert et al 1994;Baguisi et al 1999;Cammuso et al 2000) and even in pigs (Shamay et al 1992). The efficiency of what has become the standard oestrogen/progesterone/dexamethasone regime was 89 % (8 out of 9 heifers on the first attempt, 100% ultimately) in this study and is similar to the efficiencies of 70-100% reported by others for prepubertal heifers (Smith & Schanbacher, 1973;Fulkerson & McDowell, 1975 ;Field et al 1979), sheep (Alifakiotis et al 1980) and goats (Cammuso et al 2000). Furthermore, in the current study there was no evidence that the presence of the transgene influenced the responsiveness of the heifer calves to the induction protocol.…”
Section: Induction Success In Heiferssupporting
confidence: 88%
“…Most studies of lactation induction in sheep have been conducted with Prealpes du Sud ewes (Kann, 1997;Kann et al, 1999;Head et al, 1980), which is a dual-purpose local French breed and not a true dairy sheep, or with local dairy ewes of a nonspecified breed (Alifakiotis et al, 1980). Kann (1997) and Kann et al (1999) concluded that the inclusion of growth hormone in the induction protocol is necessary to improve milk yield in ewes.…”
Section: Introductionmentioning
confidence: 99%
“…Although milk yields increased rapidly, they were still less than those of ewes lactating after lambing, and the number of ewes which lactated after treatment was variable. The ewes were also induced to lactate after injections of estradiol-17(3 (E 2 -(3) and P 4 at doses (0.5 and 1.25 mg/kg body weight/day, respectively) similar to (D'Amico et al, 1976 ;Alifakiotis et al, 1980) or five-fold higher (Head et al, 1980) than those used to induce cows into lactation (Smith and Schanbacher, 1973 ;Erb et al, 1976 ;Chakriyarat et al, 1978 ;Delouis et al, 1978). In these studies, the milk yields of induced ewes were less than after lambing, and the number of animals responding to the treatment varied.…”
Section: Introductionmentioning
confidence: 99%